Scientific productivity in neurology: impact of the socio-economic status - Mariotto, Sara; Mantovani, Alessandro (Neurological sciences, 2021)
Objective Scientific productivity is relevant to support clinical activity, improve therapeutic strategies, and understand the pathophysiological mechanisms of neurological disorders. We performed an updated bibliometric research to assess the country-specific relationship between neurological scientific production and socio-economic variables of dedicated resources. Methods Neurological scientific productivity of 168 countries, from 1996 to 2019, was obtained using the SCImago online website. Data on gross domestic product (GDP), percentage of GDP spent in research and development, and number of researchers per million people were obtained using the World Bank Group website. Results The USA was the first country in terms of documents produced (260,030), followed by Germany (69,841), Japan (65,200), the UK (60,914), and Italy (50,017). Except for Japan, all the most productive countries had an increase in scientific productivity in the last 12 years. In 2019, the USA still ranked first in the number of neurological papers published, followed by Germany, the UK, Italy, and Japan. Among the most productive countries, Canada and Japan did not increase the percentage of GDP spent in research over time. Except for Canada and Japan, all the most productive countries increased the number of researchers in the last years. Conclusions Our analysis provided novel evidence of the adequacy of the scientific return on country-specific investment of local dedicated resources.